1976
DOI: 10.1159/000102498
|View full text |Cite
|
Sign up to set email alerts
|

The Thalamus in the Motor System

Abstract: The ventrolateral (VL) and ventral anterior (VA) are the main thalamic relay for cerebellar and pallidal efferents going to the motor cortex. Four aspects of the function of these nuclei are briefly considered. (1) It is well known that these thalamic structures are not a simple relay on the way to the motor cortex, but that they have a gating function for the cerebellar afferents. The gating mechanism is active during slow-wave sleep, with deafferentation and with the use of various anesthetics. Possibly, it … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

1980
1980
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 43 publications
0
14
0
1
Order By: Relevance
“…Purpura (1970) suggested that this eect can be described as a functional deaerentiation. The local inhibitory in¯uence of the RN in the motor domain has also been described by Massion (1967), who considered the thalamic motor nuclei a gate that might be open or closed to a motor command.…”
Section: Inhibition Of Irrelevant Informationmentioning
confidence: 86%
“…Purpura (1970) suggested that this eect can be described as a functional deaerentiation. The local inhibitory in¯uence of the RN in the motor domain has also been described by Massion (1967), who considered the thalamic motor nuclei a gate that might be open or closed to a motor command.…”
Section: Inhibition Of Irrelevant Informationmentioning
confidence: 86%
“…A diencephalic lesion may affect contralateral limbs through bulbo spinal fibers [4,5,10,13,15,16] or by projections from VL thalamus, through the overlying cortex, to the contralateral spinal cord [19,27], The lesion may have an ipsilateral effect mediated through uncrossed de scending projections (corticospinal [24,34] or bulbospinal [5,13,15,16] fibers): alternatively the lesion may affect motor mechanisms on ¡he other side of the brain [5,6,14,20,29,36] which in turn exert a (crossed) in fluence on segmental neurons ipsilateral to the lesion. In particular, the lesion could exert bilateral effects through connections within the brain stem that link the two sides of the reticular formation and through others linking the basal ganglia and thalamus on one side of the brain with sub cortical structures on the other [5,12,18,23,28,30,32], Patients improved in using the arm ipsilateral to surgery, although there was no obvious improvement in its tremor or rigidity.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, for the drawing test, the lesion's initial effect (during pre5/ postl) was to improve the contralateral arm more than the ipsilateral one, whereas, for the pegboard test, the contralateral arm tended to be worse directly after surgery while the ipsilateral arm was unchanged. This initial deterioration in timed performance of the contralateral arm was associat ed with a transient dysmetria clinically apparent in some patients while using the limb for the pegboard test on postl, and presumably reflecting a disturbance of pathways that carry proprioceptive and visual feedback to the thalamus and motor cortex [3,7,19,22]. Such a disturbance of coor dination would affect performance with the pegboard rather than the bal listic movement involved in the drawing test.…”
Section: Discussionmentioning
confidence: 99%
“…The properties of the neurons which we designate as type A are similar to those described [1,6,8,12,[19][20][21]23] for "motor" neurons in the ventrobasal complex of the human thalamus, which respond to the performance of voluntary movements, and have been called "voluntary movement" cells [9]. The involvement of these elements of the ventrolateral nucleus of the thalamus in transmitting information during processing of conditioned reflex operant movements is also indicated by results obtained in animal experiments [7,11,14,15,22].…”
Section: Discussionmentioning
confidence: 87%
“…The appearance of dynamic cross-correlation relationships between close-lying neurons in these functional stages of voluntary movements can evidently be taken to support the existence of an interaction between cellular elements. Considering the close morphological connections of the ventrolateral nucleus [10,14,16,18] with the cerebral cortex, with underlying subeortical structures, and intralaminar formations, it can be suggested that the multicomponent patterns of network activity of A and B cells reflect their simultaneous complementary responses to facilitation and/or inhibition of influences from different sources arising during performance of a voluntary movement. It was typical that the interconnected changes in activity in both kinds of ceils did not correlate with the performance of any particular movement, its type, or somatotopic properties.…”
Section: Discussionmentioning
confidence: 99%